Knowledge Analysis Of Pregnant Women On Prevention The Transmission Covid 19 - Sri Wahyuni Bahrum; Irma Sri Rejeki; Fadlyatul Fajri; Nurnainah Nurnainah; Rahil Atika; Cengiz Kayacilar (CV. Inara, 2021)
Pregnant women are people with a high risk of contracting COVID 19, this is because pregnant women have a low immune system, making them more susceptible to disease or infection. Analysis of Knowledge Pregnant Women to the Prevention of Covid 19 Transmission in the Work Area of ​​the Public Health Bontomate'ne, District Jeneponto. The type of research used is quantitative with a descriptive research design using a cross sectional approach. To determine the relationship between the independent variable and the dependent variable by using joint measurements, the total population is 30 people, the sampling of this study uses purposive sampling technique so that the results are 30 respondents, the data measurement tool uses a questionnaire. Chi-square test obtained p-Value = 0.01, which means it is smaller than <0.05. There is a relationship between. knowledge and prevention of Covid-19 transmission to pregnant women at the Bontomate'ne Health Center, Jeneponto Regency.